T2-weighted Imaging Features of the Fetal Thymus in the Middle and Late Pregnancy: A Post-mortem Study based on Magnetic Resonance Imaging - Yuan, Leilei; Lv, Baohua; Wang, Han; Wang, Zhaohua; Shang, Hua; Li, Xiujuan; Liang, Lisha; Lin, Xiangtao (Current Medical Imaging, 2024)
Background Fat-suppressed (FS) T2-weighed turbo spin-echo (TSE) sequence was used to detect the signal of the thymus and the characteristics of the thymus location, measure the two-dimensional diameter at specific levels, and analyze the association with gestational weeks. Methods This study involved 51 fetal specimens. Post-mortem MRI scanning was implemented with a 3.0-T MRI system. T2-weighted imaging (T2WI) features of the thymus in fetuses were quantitatively investigated with DICOM images. Statistical analysis was done with the Chi-Square test, one-way ANOVA, and Student’s t-test. Results There was heterogeneity in the morphology of the fetal thymus. FS T2-weighted TSE sequence clearly exhibited the microstructure of the fetal thymus. The thymus extensively showed a lobulated appearance. The central signal is much higher than the peripheral signal in each lobule. In addition, FS-T2WI images can clearly show the interlobular septum, which is filled with fluid and presents a linear high signal. The signal intensity of fetal thymus increased with gestational weeks. The diameter measured in a particular plane was highly correlated with gestational week. Conclusion FS T2-weighted TSE sequence provides high-resolution images of the fetal thymus. The change in signal intensity, location, and two-dimensional diameter in a specific plane can be used as a research direction for the fetal thymus.
Keywords: Antenatal diagnosis